DIFFERENCES IN MEN’S AND WOMEN’S ESL ACADEMIC WRITING AT THE UNIVERSITY OF MELBOURNE - Dana Waskita (Fakultas Seni Rupa dan Desain ITB, 2008)
This study examines men’s and women’s ESL academic writing in their written assignments at the University of Melbourne. Three sets of men’s and women’s academic writing were analyzed for several common features of academic writing including syntactic complexity, means of integrating cited information, and methods of presenting arguments. The findings showed significant differences between the men’s and women’s texts in those three aspects. The structure of the women’s texts tended to be more complex than the men’s. The women also used more paraphrases to integrate cited information, and presented better organized arguments. Those characteristics of the women’s texts presumably would be advantages for their success in academic writing, and indicate a higher level of proficiency in ESL academic writing.